Planning pedagogical practice using video as a didactic resource in mathematics education (Revista BOEM, 2024)
In the educational context and with the emergence of new technologies, new ways of learning and acquiring knowledge have arisen, prompting reflections on the didactic and methodological possibilities of using technological resources in the teaching and learning process. Among these technologies, video, due to its content presentation and arrangement and its ability to spark the imagination, has become an important tool gaining relevance in Mathematics Education. The use of this resource requires teachers not only to have knowledge and critical analysis of its content but also to plan when and how to use it in their practice. Consideringthis, this article presents a methodology to assist mathematics teachers in planning pedagogical practice using video media. A lesson plan will be presented, with a pedagogical and technical approach to using video media. The contributions of the plan areoptimizing time for planning practices using videos; understanding the pedagogical and technical aspects of the media; appropriately using audiovisual resources in the educational process of mathematics teaching; encouraging the use of videos in mathematics classes; and providing confidence in selecting the topic to be covered, based on curricular guidelines and utilizing media resources.
Keywords: lesson plan; educational video; mathematics teaching